Enhanced performance of non-thermal plasma coupled with TiO(2)/GAC for decomposition of chlorinated organic compounds: influence of a hydrogen-rich substance - Abedi, Kamaleddin (BioMed Central, 2014)
BACKGROUND: No study was found in the literature on the combination of TiO(2)/GAC catalyst and non-thermal plasma for chlorinated volatile organic compounds abatement in air. This paper presents this hybrid process for the decomposition of chloroform (as a target compound) using a multi-pin to plate discharge reactor. The experiments were performed using a high frequency pulsed transformer as the power supply system to examine the effect of SIE, frequency, as well as initial concentration on the chloroform removal efficiency (RE). Toluene was added as a hydrogen-rich source to shift the reactions into the formation of environmentally desirable products. RESULTS: RE of around 60% was observed with the NTP-alone process at the highest possible SIE (3000 J L(−1)), while it rocketed up to 100% (total oxidation) in the presence of TiO(2)/GAC at SIE of 1000 J L(−1). About 100% O(3) destruction over TiO(2)/GAC and both adsorption and catalytic activities of GAC may be considered as the reasons for better performance of the hybrid process. Toluene feeding diminished the chlorinated by-products such as Cl(2) and TCE significantly. The selectivity towards CO(2) was noticed to enhance noticeably, when both catalyst and toluene were introduced, regardless of the input concentration. CONCLUSIONS: Our findings suggest that the hybrid of NTP with TiO(2)/GAC will highly be effective in the abatement of chloroform, and the addition of toluene will successfully decline harmful chlorinated by-products.